2019
DOI: 10.24042/tadris.v4i2.4893
|View full text |Cite
|
Sign up to set email alerts
|

Management System of Education: Conceptual Similarity (Integration) between Japanese Learning System and Islamic Learning System in Indonesia

Abstract: The changing times that followed the development of technology made the education system management must be updated to suit the needs and conditions of the environment. In this article, we look for information about the education system in two different countries, namely Japan and Indonesia. The purpose of this research is to find out the integration between the two countries that have different education management systems. The research method used is a descriptive qualitative method. In this research also, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
6
1
3
Order By: Relevance
“…The SAVI learning model has an impact on increasing students' learning interest and learning achievement (Rahmawati, R., Lestari, F., & Umam, R. 2019), problem solving, and student learning outcomes (Yulianti, Haris, and Chandra 2018;Nur Agustina, Yurniwati, and MS 2019;Setyani, Nizardin, and Utami 2019;Sulakasana , Margunaasa, and Authority 2018;Dewi, Murda, and Pudjawan 2019). Different from previous studies, our research has proven that the SAVI and SNOWBALLING learning models actually have an impact on the numerical ability of students (Munifah, Tsani, I., Yasin, M., Tortop, H. S., Palupi, E. K., & Umam, R. 2019), and the most effective is the SAVI learning model.…”
Section: Resultscontrasting
confidence: 94%
“…The SAVI learning model has an impact on increasing students' learning interest and learning achievement (Rahmawati, R., Lestari, F., & Umam, R. 2019), problem solving, and student learning outcomes (Yulianti, Haris, and Chandra 2018;Nur Agustina, Yurniwati, and MS 2019;Setyani, Nizardin, and Utami 2019;Sulakasana , Margunaasa, and Authority 2018;Dewi, Murda, and Pudjawan 2019). Different from previous studies, our research has proven that the SAVI and SNOWBALLING learning models actually have an impact on the numerical ability of students (Munifah, Tsani, I., Yasin, M., Tortop, H. S., Palupi, E. K., & Umam, R. 2019), and the most effective is the SAVI learning model.…”
Section: Resultscontrasting
confidence: 94%
“…Based on the results of the study showed that the flipped classroom model is better to use than the heuristic vee model. This is shown in the first step of the flipped classroom model using video or other technology-assisted teaching materials to make students interactive with the material to be taught (Munifah, Tsani, et al, 2019). In the vee heuristic model, the teacher is still the main instructor without intermediary media that makes students feel bored with the learning activities undertaken (Huda, Syahrul, Firmansyah, Ramadhani, & Prasetiyo, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The facts gathered here are in the form of arguments from some students which are then discussed to find solutions to the problems given (Munozfritis, 2019). The level of mathematical creative thinking ability in PBL models is increased through the stage of analyzing a problem (Munifah et al, 2019a;Munifah, Romadhon, Ridhona, & Ramadhani 2019;Munifah et al, 2019c). On the other hand, in ATI model, the goal is achieved through the stage where the teacher provides initial treatment to students as an introduction that will trigger the emergence of students' creative thinking abilities (Syahrir et al, 2019).…”
Section: Discussionmentioning
confidence: 99%